Pengaruh Budaya Religius dan Program Ubudiyah terhadap Pembinaan Akhlak Siswa SMPIT Assalamah Jakarta - Kamal, Addin Mustofa; Atmowidjoyo, Sutarjo; Syairozi, Ishak (Universitas Indraprasta PGRI Jakarta, 2024)
The research aims to assess how much the influence of religious cultural values through the ubudiyah program have on developing students' morals and to identify obstacles that may occur in its implementation. The research methodology used is a quantitative approach using a questionnaire as a data collection instrument. The research sample consisted of 38 students from various grade levels at SMPIT Assalaamah. The collected data was analyzed using descriptive statistical techniques and regression analysis to test the relationship between the variables studied. The partial test results show that religious culture has a positive effect on moral development. With a = 0,05, religious culture shows a significance value of 0,000 (0,000< 0,05) with a t count of 4,211. So 4,211 is greater than the t-table data obtained, which is 1,688 (4,211>1,688). Partial test results show that the Ubudiyah program has a significant positive influence on moral development. With a= 0,05, the Ubudiyah program achieves higher correlation and influence values. The ubudiyah program shows a significance value of 0,000 (0,000 < 0,05) with a calculated t of 6,785, making 6,785 greater than the data obtained from the t table, which is 1,688 (6,785 > 1,688). The implication of this research is the need to increase teacher supervision and understanding as well as the active participation of students in religious programs to maximize their impact in coaching and forming students' morals.